2012
DOI: 10.4269/ajtmh.2012.12-0171
|View full text |Cite
|
Sign up to set email alerts
|

Treatable Bacterial Infections Are Underrecognized Causes of Fever in Ethiopian Children

Abstract: Abstract. Febrile illnesses remain a major cause of morbidity and mortality in resource-poor countries, but too often, tests are not available to determine the causes, leading to misdiagnosis and inappropriate treatment. To determine the cause of febrile illnesses, we recovered the malaria smears from 102 children presenting with fever to Soddo Christian Hospital in Wolaitta Soddo, Ethiopia. DNA was isolated from the smears and evaluated by real-time polymerase chain reaction. We identified pathogen DNA with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 23 publications
(24 reference statements)
0
15
0
Order By: Relevance
“…The significance of the present study is further strengthened through recent reports of SFG rickettsiae in humans in Ethiopia, including R. africae in a French man who stayed for 2 months in western Ethiopia (Stephany et al, 2009) and 2.9% (3/102) SFG Rickettsia DNA in dried thin blood smears prepared to test for malaria in children with febrile illnesses at Soddo Christian Hospital in Wolaitta Soddo in southern Ethiopia (Aarsland et al, 2012).…”
Section: Zonesmentioning
confidence: 49%
“…The significance of the present study is further strengthened through recent reports of SFG rickettsiae in humans in Ethiopia, including R. africae in a French man who stayed for 2 months in western Ethiopia (Stephany et al, 2009) and 2.9% (3/102) SFG Rickettsia DNA in dried thin blood smears prepared to test for malaria in children with febrile illnesses at Soddo Christian Hospital in Wolaitta Soddo in southern Ethiopia (Aarsland et al, 2012).…”
Section: Zonesmentioning
confidence: 49%
“…[ 5 , 6 , 25 – 43 ] The median (range) number of diagnostic tests meeting our confirmed laboratory case definitions was 2 (1 to 11) per study. Of the 45 eligible studies, 8 (17.8%) studies did not meet our inclusion criteria for all of the infectious diseases investigated in the study, with results for those diseases excluded from our analysis ( Table 3 ) [ 3 , 25 , 29 , 30 , 36 , 44 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of nine studies investigating bacterial zoonoses, six (66.7%) studies met our pre-defined testing criteria for rickettsial infection [ 3 , 4 , 43 , 44 , 46 , 57 ] and five (55.5%) studies met the pre-defined criteria for leptospirosis [ 3 , 4 , 44 , 58 , 59 ]. In one study from South East Asia investigating febrile children at a tertiary referral urban children’s hospital and a rural provincial hospital, of 14 confirmed leptospirosis cases, 10 (71.4%) were from patients at the rural hospital [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using radiobinding assays to assess tTG autoantibodies with proven high diagnostic sensitivity and specificity for celiac disease [8,12,34,35]. Moreover, radioligand binding assays have been used in several previous prospective screening studies for celiac disease [8,35] and proven the best performance as compared to other ELISAs in an international tTG workshop [36]. In various previous studies, it was demonstrated that the serum IgG level is decreased during pregnancy since it cross placenta to prevent the fetus [37,38].…”
Section: Discussionmentioning
confidence: 99%